AI in Business and Economics - Isabel Lausberg; Michael Vogelsang (De Gruyter, 2024)
Rapid advances in artificial intelligence (AI) technologies have generated intense interest and debate about their potential to reshape industries, labour markets and socio-economic structures. This volume presents a collection of academic papers stemming from'The Economic Perspective of Artificial Intelligence'(EPEAI) conference held at the Ruhr West University of Applied Sciences in Mülheim an der Ruhr, Germany, in March 2023. AI in Business and Economics discusses topics as varied as marketing, accounting, reporting, business narratives, forecasting, generational differences in attitudes, economic policy – all in the context of exploring the multifaceted intersection of economics and artificial intelligence. It navigates through the fog caused by the heterogeneity of diverse AI applications and methodologies by examining artificial intelligence from an economic perspective. In doing so, it becomes clear that the implementation of a broad range of AI technologies in companies has just begun. Businesses, employees, and policy makers will soon have to adapt to the fast-paced advancements in artificial intelligence, ensuring they become and remain competitive, ethical, and forward-thinking in a changing global landscape. This book will serve as a valuable resource for scholars, practitioners, and students exploring the complexities of the economic implications of AI.